PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MALANG UTARA - Riska Widia Rantasari; Nur Hidayati; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTIONThe purpose of this study was to determine the level of effectiveness in tax collection with a letter of reprimand and a forced letter against taxpayers who did not pay off tax debts that exceeded the due date of repayment in order to increase tax revenues in North Malang KPP Pratama.This study uses library research methods and original data retrieval by interviewing and discussing directly with the Chief Executive of the Billing Session at North Malang KPP Pratama.The sample used 36 months, the analysis used in this study used multiple linear regression analysis with the help of SPSS version 16 and the method of measuring the results of the study using the ratio scale. Based on the analysis carried out, it can be concluded that simultaneous reprimand letters and forced letters have a significant effect on the increase in tax revenues in North Malang KPP Pratama. Whereas in a formal manner reprimand letters and forced letters have a significant effect on increasing tax revenues in North Malang KPP Pratama.Keywords: Reprimand, Forced Letter, Increased Tax Revenue.